Development of a Web-Based Reservation System to Improve the Efficiency of Catering Services - Rachell Intanio Sahara; Risa Chairunnisa; Muchamad Iqbal Muchamad Iqbal; Azmi Hardi Azmi Hardi Roza (Komunitas Dosen Indonesia, 2025)
Digital transformation has become essential for improving service efficiency across various sectors, including micro, small, and medium enterprises (MSMEs) in the catering industry. Manual reservation processes often cause service delays, inaccurate data recording, and decreased customer satisfaction. This study aims to develop a web-based catering reservation system to automate bookings, streamline service management, and improve interactions between service providers and customers. The system was developed using the Agile Software Development methodology with the Scrum framework, which supports iterative, adaptive development and active user involvement. A User-Centered Design (UCD) approach was also adopted to ensure usability and alignment with user needs. The development process involved requirement analysis, system and interface design using UML, implementation with Laravel and MySQL, and evaluation through Black Box Testing and User Acceptance Testing (UAT). The system provides core features such as menu ordering, transaction management, payment confirmation, and report generation, all presented in a responsive and accessible interface. Results show that the system improves service efficiency and enhances user satisfaction, particularly in terms of system navigation, clarity of information, and ease of use. However, the study has limitations, including its application within a single MSME environment and the absence of advanced features like automated notifications or integrated digital payments. These contextual constraints limit the generalizability of findings. In conclusion, the developed system contributes to the digitalization of catering services and offers promising potential for broader application. Future research should explore scalability across various MSME types and enhance system capabilities to meet wider operational demands.